An integrated approach to the audit procedures to be followed during the implementation of Product Data Management (PDM) software - George, Sam; K.David, Dr (International Journal of Engineering and Technology, 2018)
Product Data Management (PDM) is a domain which comes under the umbrella of Product Lifecycle Management (PLM).  While PLM covers entire life cycle of the structure taken for consideration, PDM focus only the hardware portion of it.   The implementation of a system which involves product life cycle is a challenging process as it involves an entire changeover of existing working procedures. Moreover, this works in a domain which is dispersed geographically across multiple locations across the globe. In this context, diversification is keyword during the entire phase of operation.  This context throws open challenges to find uniformity in procedures, practices, guidelines and documentation in every phase. The first step in defining uniformity is adhering to certain standards and practices which are universally acclaimed. In this context, procedures and directives mentioned in International Standards Organisation (ISO) and Information Systems Audit and Control Association (ISACA) become handy.  Audit procedures can be broadly classified in PDM domain as direct and indirect. Direct audit practices are procedure, document and resource oriented while indirect audit focus on finance and infrastructure. In most phases there shall be overlapping relations between these two areas.  Management of these aspects is discussed in individual phases of this engineering domain.